Analysis of Change Behavior Prevention of Covid-19 Transmission Based on Integrated Behavior Model - Triyanto, Endang; Kusumawardani, Lita Heni (Jurnal Keperawatan Soedirman, 2020)
Introduction: Covid 19 pandemic forces people to limit their activities to prevent the spread of the virus. Covid 19 transmission prevention behaviors that can be done include: washing hands using soap and running water, using masks when leaving the house and doing social distancing. This health behavior based on the integrated behavior model theory is influenced by many factors, including demographic factors, knowledge, past habits, attitudes, norms, environment and media.Objective: For analyze changes in Covid 19 transmission prevention behavior in terms of the integrated behavior model.Method: The research method used by survey. A total of 103 respondents in Banyumas obtained by convenience sampling in April to May 2020. Statistical analysis used with frequency distribution.Result:The data obtained were age dominated in the range of 21-59 years as many as 68 people or around 66%, the majority of high school graduates are 76 people or around 74%, urban areas are 63% and rural are 37%. Handwashing behavior used soap and running water very well reaches 84.5%. The used of masks when leaving the house was 92.2%. The application of social distancing was only 47.6%. Public knowledge about Covid 19 good categories reached 81.5%. Positive attitude as many as 80 people or about 77%. The application of norms/ rules reaches 100%. The availability of supporting facilities is 92%. 75% of media accessibility. Only 10% of the community previously had the habit of washing their hands and wearing masks.Conclusion: A person's behavior is influenced by demographic factors, knowledge, attitudes, norms, habits, environment, media. These factors become a unity that influences each other until the creation of new expected behavior.